Good continuation in 3D: the neurogeometry of stereo vision - Bolelli, Maria Virginia; Citti, Giovanna; Sarti, Alessandro; Zucker, Steven W. (Frontiers in Computer Science, 2024)
Classical good continuation for image curves is based on 2D position and orientation. It is supported by the columnar organization of cortex, by psychophysical experiments, and by rich models of (differential) geometry. Here, we extend good continuation to stereo by introducing a neurogeometric model to abstract cortical organization. Our model clarifies which aspects of the projected scene geometry are relevant to neural connections. The model utilizes parameterizations that integrate spatial and orientation disparities, and provides insight into the psychophysics of stereo by yielding a well-defined 3D association field. In sum, the model illustrates how good continuation in the (3D) world generalizes good continuation in the (2D) plane.